Bibliometric Analysis: Adobe Flash Cs6 Research in Mathematics Learning - Ilham Muhammad; Christina Monika Samosir; Elmawati Elmawati; Febrinna Marchy (STKIP Singkawang, 2023)
The use of animation on Adobe Flash media in learning mathematics has many benefits, especially in helping students understand mathematics more meaningfully, connecting mathematics with the real world, visualizing, and understanding the importance of mathematics. This study aims to capture the landscape of previous research that is relevant to Adobe Flash in mathematics learning in the last decade, namely from 2012 to 2022 using bibliometric analysis with the help of the VOSviewer application. The Google Scholar database was used to search for data with the keywords